1968
DOI: 10.1083/jcb.38.1.193
|View full text |Cite
|
Sign up to set email alerts
|

The Axon Hillock and the Initial Segment

Abstract: Axon hillocks and initial segments have been recognized and studied in electron micrographs of a wide variety of neurons. In all multipolar neurons the fine structure of the initial segment has the same pattern, whether or not the axon is ensheathed in myelin. The internal structure of the initial segment is characterized by three special features: (a) a dense layer of finely granular material undercoating the plasma membrane, (b) scattered clusters of ribosomes, and (c) fascicles of microtubules. A similar un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
217
1

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(241 citation statements)
references
References 18 publications
20
217
1
Order By: Relevance
“…Nevertheless other energy-intensive processes such as axonal transport by kinesin motors are readily observed in the extruded axoplasm (Kang et al 2016;Prahlad et al 2000;Vale et al 1985). Another key observation against the idea of intra-axonal protein synthesis in the squid giant axon is the absence of morphological evidence for canonical ribosomes in the giant axon, and in vertebrate axons in general (Conradi 1966;Palay and Palade 1955;Palay et al 1968;Peters et al 1968;Peters et al 1970;Zelena 1972). This is in contrast to well-documented sites of "local protein synthesis" such as in dendrites where canonical ribosomes and polyribosomes have clearly been observed (Steward and Levy 1982;Steward and Schuman 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless other energy-intensive processes such as axonal transport by kinesin motors are readily observed in the extruded axoplasm (Kang et al 2016;Prahlad et al 2000;Vale et al 1985). Another key observation against the idea of intra-axonal protein synthesis in the squid giant axon is the absence of morphological evidence for canonical ribosomes in the giant axon, and in vertebrate axons in general (Conradi 1966;Palay and Palade 1955;Palay et al 1968;Peters et al 1968;Peters et al 1970;Zelena 1972). This is in contrast to well-documented sites of "local protein synthesis" such as in dendrites where canonical ribosomes and polyribosomes have clearly been observed (Steward and Levy 1982;Steward and Schuman 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS and peripheral nervous system, SSCs are neuron specific and localized exclusively in perikarya and the most proximal portions of their processes (Rosenbluth, 1962;Henkart et al, 1976;Peters et al, 1991). Likewise, SSCs occur in perikarya and large-caliber proximal dendrites of cortical neurons (Rosenbluth, 1962;Buschmann, 1979; for review, see Peters et al, 1991) and are unique to the axon initial segment of principal cells (Palay et al, 1968;Benedeczky et al, 1994). Double arrowheads in B point to an axo-spinous synapse (ax-sp) next to the SSC.…”
Section: Methodsmentioning
confidence: 99%
“…The opaque axoplasmic material of the nodes of Ranvier has been thought to be related to specialized zones of membrane permeability (5), to areas of activity (17), or to diffusion barriers (I). A dense layer of fine granular material undercoating the plasma membrane of the axon initial segment, resembling that found at the node of Ranvier, has also been described in different neurons (13,22). It has been suggested that this undercoating represents a structural modification of the cell surface involved in the origin and propagation of the action potential (13).…”
mentioning
confidence: 99%
“…A dense layer of fine granular material undercoating the plasma membrane of the axon initial segment, resembling that found at the node of Ranvier, has also been described in different neurons (13,22). It has been suggested that this undercoating represents a structural modification of the cell surface involved in the origin and propagation of the action potential (13). The distribution of the thickenings along the axolemma has been compared to that found, with the aid of histochemical techniques, in connection with sites of Na+-K+-Mg++-ATPase (19) and of acetylcholinesterase activities (26).…”
mentioning
confidence: 99%